Public health workforce survey data (2016–2021) related to employee turnover: proposed methods for harmonization and triangulation - Weiss, Nicole M.; Martin, Skky; Onal, Sezen O.; McDaniel, Nicole; Leider, Jonathon P. (Frontiers in Public Health, 2024)
Introduction Public health workforce numbers are unsustainable at best and dire at worst: based on 2017 and 2019 data, 80,000 FTEs needed to be hired by health departments to provide basic public health foundational services before COVID-19 hit, suggesting that the situation is worse after the mass exodus of public health officials due to the pandemic. As such, a better understanding of public health workforce turnover is critical to improving recruitment and retention in the discipline. Methods This methods report details how the authors harmonized four public health workforce surveys—the Public Health Workforce Interests and Needs Survey (PH WINS), the National Association of County and City Health Officials (NACCHO) Profile, the NACCHO Forces of Change survey, and the Association of State and Territorial Health Officials (ASTHO) Profile—in order to examine employee turnover. Results We found that 31% of the public health workforce reported considering leaving their positions at some time in the future. Furthermore, the majority of agencies reported that zero vacancies had been filled in both 2018 and 2019. Discussion These findings suggest that retention, recruitment, and onboarding may be areas upon which to focus evaluation and quality improvement endeavors, allowing public health organizations to better attract and retain the most qualified candidates.